Framing Analysis In Media Television News MetroTVOne Related Arrest by the Chairman MK Akil Mocktar Commission Case of Corruption - Aryadi, Aryadi (Universitas Semarang, 2014)
Aryadi, G331.10.0018.Framing Analysis In Media Television News Metro TVOne Related Arrest by the Chairman MK Akil Mocktar Commission Case of Corruption Skripsi : Program S1 of Communication University of Semarang.This research aims to understand how the framing of television-related news in the arrest of thechairman of the Constitutional Court AkilMocktar by the Commission on cases of corruption. Impressions is catching news MK chairman AkilMocktar on Metro TV and TVOne. Theoretical foundation, framing analysis model of Murray Edelman, the theory is used to understand the reality of diverse and irregular into a reality that has meaning, using the categorization, the use of a particular perspective with certain words is also a word that signifies how the facts or reality understood.Qualitative research methods and strategies for framing the analysis, the study was conducted by observing the video sempel news on Metro TV and TVOne selected.Based on the research results, the general conclusion of each media that Metro TV and TVOne has a different way of constructing a bribery case Mocktar chairman MK Akil is in its message. Metro TV tend to highlight cases of bribery Court of facts, Metro TV does not describe the alleged emerging society. While TVOne looks construct audiences with growing allegations in the news